Unraveling the Twin and Tunability of the Crystal Domain Sizes in the Medium‐Pore Zeolite ZSM‐57 by Electron Crystallography. Issue 4 (12th December 2018) - Wang, Lei; Yan, Nana; Liu, Xiaona; Zhao, Xuebin; Shen, Meikun; Liu, Leifeng; Tian, Peng; Guo, Peng; Liu, Zhongmin
Abstract: Tailoring the morphology of a specific crystalline material through distinct crystal growth mechanisms (classical and nonclassical) is challenging. Herein, we report the two unique morphologies of a medium‐pore (10×8‐ring) zeolite, ZSM‐57, prepared by employing an identical organic structure‐directing agent (OSDA) and different inorganic cations, namely Na + and K +, denoted as ZSM‐57‐Na (pentagonal nanoplates) and ZSM‐57‐K (pentagonal nanoprisms), respectively. The tunable twin domain size and twin boundaries in both samples have been unraveled at the atomic level by electron crystallography. It is of significance to note that the 10‐ring pore openings run perpendicular to the pentagonal nanoplates and nanoprisms. Moreover, the distinct crystal growth mechanisms, which result in the different unique morphologies and tunable twin domains, were further determined by electron crystallography combined with other techniques. Nonclassical growth involving the aggregation of amorphous aluminosilicate nanoparticles to the smooth ZSM‐57‐Na crystal surface dominates the ZSM‐57‐Na crystallization process. For the ZSM‐57‐K sample, the classical layer‐by‐layer growth through the addition of silica molecules to advancing steps on the crystal surface dominates the ZSM‐57‐K crystallization process. The different morphologies of both samples result in the distinct catalytic lifespan of the methanol conversion and selectivity of lower olefins. Abstract : Bridging the gap : Tunable nonclassical and classical crystal growth mechanisms in the ZSM‐57 zeolite have been revealed with the aid of electron crystallography (see figure). The different mechanisms lead to zeolites with different unique morphologies and twin domains than can be tuned by varying the metal cation in the reaction medium. The methanol conversion reaction revealed the two zeolites with different morphologies exhibit different catalytic behavior.